A correlation study of fear of cancer recurrence, illness representation, self-regulation, and quality of life among gynecologic cancer survivors in Taiwan - Li-Yun Tsai; Shu-Chen Lee; Kung-Liahng Wang; Shiow-Luan Tsay; Jung-Mei Tsai (Elsevier, 2018)
Objective: The purpose of this study was to examine the correlations among fear of cancer recurrence (FCR), illness representation (IR), self-regulation (SR), and quality of life (QOL) in gynecologic cancer survivors. Materials and methods: A cross-sectional study was conducted with 287 participants recruited from a medical center in northern Taiwan. Four questionnaires, the Assessment of Survivor Concerns (ASC), the Brief Illness Perception Questionnaire (BIPQ), the Self-Regulation Questionnaire (SRQ), and the European Organization for Research and Treatment of Cancer's Quality-of-Life Questionnaire-Core 30-item (EORTC QLQ-C30), were used to assess FCR, IR, SR, and QOL respectively. Data pertaining to socio-demographic characteristics and self-reported medical status was also collected from the participants. Stepwise regression analysis was performed to identify predictors of QOL. Results: The results showed that FCR (r = −.21, P < .01) and IR (r = −.44, P < .01) was negatively correlated with global QOL subscale of the EORTC QLQ-C30. SR, IR, and health status in the self-reported medical status explained 39% of the variance in global QOL, with SR of the largest. Conclusions: Our findings provided valuable information to healthcare professionals about the ability of SR to affect QOL and negative impacts of FCR and IR on gynecologic cancer survivors. Keywords: Gynecologic cancer survivors, Fear of cancer recurrence, Illness representation, Self-regulation, Quality of life